2016
DOI: 10.1002/jee.20150
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate Students' Beliefs about Engineering Problem Solving

Abstract: Background Problem solving is considered to be a central activity of engineering practice. While some studies have shown how various beliefs affect students' abilities to solve problems, studies are needed that explicitly examine the beliefs and assumptions students bring to the problem‐solving process. Purpose/Hypothesis The purpose of this qualitative research was to describe students' engineering problem‐solving processes and develop a conceptual model that illustrates students' beliefs about problem solvin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
84
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(103 citation statements)
references
References 58 publications
2
84
0
Order By: Relevance
“…In addition, EDA will not associate to these topic emotions for each of the design activities. This hypothesis is based on the premise engineering education researchers have suggested that engineering design problem solving may be more cognitively focused when using Piagetian constructivist tasks and activities (McNeill, Douglas, Koro-Ljungberg, Therriault, & Krause, 2016). As such, cognitive processes may suppress emotional responses (Kleinginna & Kleinginna, 1981) regardless of topic or instructional format.…”
Section: Research Goals and Hypothesismentioning
confidence: 99%
“…In addition, EDA will not associate to these topic emotions for each of the design activities. This hypothesis is based on the premise engineering education researchers have suggested that engineering design problem solving may be more cognitively focused when using Piagetian constructivist tasks and activities (McNeill, Douglas, Koro-Ljungberg, Therriault, & Krause, 2016). As such, cognitive processes may suppress emotional responses (Kleinginna & Kleinginna, 1981) regardless of topic or instructional format.…”
Section: Research Goals and Hypothesismentioning
confidence: 99%
“…Specifically, this work captured student variation in seven discrete categories that varied by students' reactions to ambiguity and their use of multiple perspectives. While prior work has shown that there is variation in how students perceive their project experiences (Atman et al, ; Courter et al, ; Douglas et al, ; McNeill, Douglas, Koro‐Ljungberg, Therriault, & Krause, ), this work provides a more nuanced characterization of the detailed variation in student experience.…”
Section: Discussionmentioning
confidence: 94%
“…use of multiple perspectives. While prior work has shown that there is variation in how students perceive their project experiences (Atman et al, 1999;Courter et al, 1998;Douglas et al, 2012;McNeill, Douglas, Koro-Ljungberg, Therriault, & Krause, 2016), this work provides a more nuanced characterization of the detailed variation in student experience. Prior literature has established that one of the most cognitively challenging aspects of solving ill-structured problems is dealing with ambiguity (Atman et al, 1999;Atman et al, 2010;Stevens et al, 2008).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In contrast, the problems encountered in the engineering workplace are "ill-structured and complex" 2 . Additional research has found that engineering students also recognize this difference: they describe the problems they see in their courses as "closed-ended, contrived, and focused on mathematics", while problems encountered in the workplace are described as "complex, open-ended, and requiring the consideration of diverse criteria" 3 .…”
Section: Introductionmentioning
confidence: 99%